Flexible and Stretchable Photonic Sensors Based on Modulation of Light Transmission. Issue 12 (29th April 2019) - Peng, Wang; Wu, Hao
Abstract: Emerging technologies, such as soft robotics, electronic skin, wearable devices, and flexible display, demand the practical application of photonic sensors that are bendable and stretchable, as conventional photonic sensors are fabricated with rigid materials and substrates, rendering their applications in deformable state or soft systems infeasible. Thus, the development of flexible and stretchable photonic sensors, which can be wrapped onto curved surfaces and easily deformed into different shapes and sizes, has inspired great research interest. This article presents recent progress in the development of flexible and stretchable photonic sensors, particularly photonic sensors based on the modulation of light transmission, from the aspects of materials synthesis and selection, structure design, fabrication methods, sensing characteristics, and performances. The challenges and future research opportunities related to flexible and stretchable photonic sensors and their potential application prospects are also discussed. Abstract : Recent progress in the development of flexible and stretchable photonic sensors, particularly photonic sensors based on the modulation of light transmission, is summarized here from the aspects of materials synthesis and selection, structure design, fabrication methods, sensing characteristics, and performances. The challenges and future research opportunities related to flexible and stretchable photonic sensors and their potential application are also discussed.